Transparency and controlling corruption (مجلة المنصور, 2022)
Through the changes that the world has witnessed in the past few years, and as a result of suffering from the negative effects of the phenomenon of corruption, which has escalated according to those changes.Many of studies found that main points which guide to reform and to reduce the effect of corruption around the world worked in three dimensions:1. (Transparency)2. (Accountability)3. Economic and political (competitive)Which play the very important role in society to rebuild the good-governance in all institutions, and empowerment people to gain the fruit of sustainable human development. Through measurement one of the most bad phenomenon in the history.